Hubungan Intensitas Penggunaan Media Online dan Citra Merek dengan Loyalitas Konsumen Koran Suara Merdeka - Anggun Puspa Regita; Djoko Setyabudi (Interaksi Online, 2020)
This study aims to determine the relationship between the intensity of the use of online media and brand image with Consumer Loyalty of Suara Merdeka Newspaper. The population in this study is Semarang residents who subscribe to the Suara Merdeka newspaper. The results showed that the intensity of the use of online media does not have a significant effect with the consumer loyalty of Suara Merdeka newspaper as indicated by the significance value 0,295 (>0,05) so the first hypothesis is rejected. Then the second hypothesis test was obtained that the brand image have a significant effect with the consumer loyalty of Suara Merdeka newspaper because the test results showed a significance value 0,028 (<0,05) so that the second hypothesis was accepted